HYSTEROTHYLACIUM KARANIENSIS N.SP. (NEMATODA: ANSAKIDAE) FROM THE BODY CAVITY OF THE SHARK, SCOLIODON PALASORRAH (CUVIER) - RAJYALAKSHM, INUGANTI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
A new species of a nematode of the family Anisakidae Railliet et Henry, 1912 from the body cavity of shark, Scoliodon palasorrah (Cuvier) from (Bay of Bengal) Visakhapatnam. The new species is characterized by body measurements, arrangement of papillae on the lips, type of striations on the cuticle, length of intestinal caecum, position of vulva, number and arrangement of caudal papillae, position and size of spicules and shape of tail. The new species is named as Hysterothylacium karanensis.